PENGARUH FAKTOR DEMOGRAFI DAN FINANCIAL TECHNOLOGY TERHADAP KINERJA KEUANGAN PADA UMKM DI KOTA MAKASSAR YANG DIMEDIASI OLEH INKLUSI KEUANGAN - eka pratiwi; Raprayoga, Rusdi (Study of Scientific and Behavioral Management, 2025)
This study aims to examine the influence of demographic faktors and financial technology on financial performance in MSMEs in Makassar City mediated by financial inclusion. This study discusses the conditions of society that are encouraged to survive in the economic situation by establishing small and medium enterprises (MSMEs) which are influenced by several faktors, namely demographic faktors and financial technology to assess financial performance mediated by financial inclusion faktors. This study is an associative type of research with a sample of 130 respondents. The data analysis technique uses Smart PLS. The results of this study indicate that demographic faktors and financial technology have a positive and significant effect on financial performance mediated by financial inclusion.